Functions of Two Distinct “Prolactin-Releasing Peptides” Evolved from a Common Ancestral Gene - Tachibana, Tetsuya; Sakamoto, Tatsuya (Frontiers in Endocrinology, 2014)
Prolactin-releasing peptide (PrRP) is one of the RF-amide peptides and was originally identified in the bovine hypothalamus as a stimulator of prolactin (PRL) release. Independently, another RF-amide peptide was found in Japanese crucian carp and named Carassius RFa (C-RFa), which shows high homology to PrRP and stimulates PRL secretion in teleost fish. Therefore, C-RFa has been recognized as fish PrRP. However, recent work has revealed that PrRP and C-RFa in non-mammalian vertebrates are encoded by separate genes originated through duplication of an ancestral gene. Indeed, both PrRP and C-RFa are suggested to exist in teleost, amphibian, reptile, and avian species. Therefore, we propose that non-mammalian PrRP (C-RFa) be renamed PrRP2. Despite a common evolutionary origin, PrRP2 appears to be a physiological regulator of PRL, whereas this is not a consistent role for PrRP itself. Further work revealed that the biological functions of PrRP and PrRP2 are not limited solely to PRL release, because they are also neuromodulators of several hypothalamus-pituitary axes and are involved in some brain circuits related to the regulation of food intake, stress, and cardiovascular functions. However, these actions appear to be different among vertebrates. For example, central injection of PrRP inhibits feeding behavior in rodents and teleosts while it stimulates it in chicks. Therefore, both PrRP and PrRP2 have acquired diverse actions through evolution. In this review, we integrate the burgeoning information of structures, expression profiles, and multiple biological actions of PrRP in higher vertebrates, as well as those of PrRP2 in non-mammals.